Exosomes Derived from Bone Marrow Mesenchymal Stem Cells as Treatment for Severe COVID-19 - Sengupta, Vikram; Sengupta, Sascha; Lazo, Angel; Woods, Peter; Nolan, Anna; Bremer, Nicholas (Stem cells and development, 2020)
This prospective nonrandomized open-label cohort study addresses the safety and efficacy of exosomes (ExoFlo™) derived from allogeneic bone marrow mesenchymal stem cells as treatment for severe COVID-19. During April 2020, ExoFlo was provided to 24 SARS-CoV-2 polymerase chain reaction-positive patients at a single hospital center, all of whom met criteria for severe COVID-19 as well as moderate-to-severe acute respiratory distress syndrome. Patients received a single 15 mL intravenous dose of ExoFlo and were evaluated for both safety and efficacy from days 1 to 14 post-treatment. All safety endpoints were met with no adverse events observed within 72 h of ExoFlo administration. A survival rate of 83% was observed. In total, 17 of 24 (71%) patients recovered, 3 of 24 (13%) patients remained critically ill though stable, and 4 of 24 (16%) patients expired for reasons unrelated to the treatment. Overall, after one treatment, patients' clinical status and oxygenation improved with an average pressure of arterial oxygen to fraction of inspired oxygen ratio (PaO /FiO ) increase of 192% ( < 0.001). Laboratory values revealed significant improvements in absolute neutrophil count [mean reduction 32% ( value <0.001)] and lymphopenia with average CD3 , CD4 , and CD8 lymphocyte counts increasing by 46% ( < 0.05), 45% ( < 0.05), and 46% ( < 0.001), respectively. Likewise, acute phase reactants declined, with mean C-reactive protein, ferritin, and D-dimer reduction of 77% ( < 0.001), 43% ( < 0.001), and 42% ( < 0.05), respectively. In conclusion, owing to its safety profile, capacity to restore oxygenation, downregulate cytokine storm, and reconstitute immunity, ExoFlo is a promising therapeutic candidate for severe COVID-19. Future randomized controlled trials (RCTs) are needed to determine ExoFlo therapeutic potential.